Does foreign finance promote the production and consumption of renewable energy in developing countries? The role of globalization - Ebaidalla M. Ebaidalla (Borsa Istanbul Review)
Given the increasing global interest in the transition to green energy sources in developing countries that have financial constraints, this study examines the influence of foreign finance on the production and consumption of renewable energy (RE). The study also explores whether globalization reinforces or weakens the impact of foreign finance on both production and consumption of RE using a sample of 88 developing countries between 1996 and 2020. The study uses advanced panel data methods including Driscoll-Kraay robust standard errors, a method of moments quantile regression (MMQR), and a generalized method of moments (GMM). The results indicate that foreign finance variables have varying effects on both the production and consumption of RE. Specifically, foreign aid and migrant remittances have a positive and significant influence on both the production and consumption of RE across various model specifications and quantiles. However, although foreign direct investment (FDI) has a positive impact on production of RE, it has no significant effect on consumption of it. Moreover, the results indicate that globalization strengthens the role of foreign aid and FDI in the production of RE. Furthermore, globalization mitigates the negative impact of remittances on production of RE, but enhances their positive effect on consumption of it. The findings highlight the crucial role of globalization in fostering the nexus between foreign finance and renewable energy in developing countries, emphasizing the role of international cooperation in promoting the transition to sustainable energy.